2015
DOI: 10.1210/jc.2014-3031
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Continuous Suppression With Once-Yearly Histrelin Subcutaneous Implants for the Treatment of Central Precocious Puberty: A Final Report of a Phase 3 Multicenter Trial

Abstract: Long-term histrelin implant therapy provided sustained gonadotropin suppression safely and effectively and improved predicted adult height in children with CPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…A subdermal implant of prolonged action that releases therapeutic doses of GnRHa for 12 to 24 months (histrelin 50 mg) has advantages and disadvantages over 1-month and 3-month depot GnRHa (52). The advantages include the abolishment of periodic subcutaneous or intramuscular administration, but the risk of reactions at the implant site, spontaneous extrusion, and local infection are the main undesirable side effects of this therapy.…”
Section: Treatment Of Central Precocious Pubertymentioning
confidence: 99%
“…A subdermal implant of prolonged action that releases therapeutic doses of GnRHa for 12 to 24 months (histrelin 50 mg) has advantages and disadvantages over 1-month and 3-month depot GnRHa (52). The advantages include the abolishment of periodic subcutaneous or intramuscular administration, but the risk of reactions at the implant site, spontaneous extrusion, and local infection are the main undesirable side effects of this therapy.…”
Section: Treatment Of Central Precocious Pubertymentioning
confidence: 99%
“…Fisher et al (41) reported the resumption of puberty in 26 of the 30 girls treated with the histrelin implant, with occurrence of menarche 2-36 months after explantation in treatment-naïve and -nonnaïve CPP girls, with an older age at explantation correlating with earlier menarche. In a recent study by Silverman et al (43), menarche occurred in two patients, 9 and 2 months after the final explant respectively.…”
Section: Reproductive Function and Risk Of Polycystic Ovarian Syndromementioning
confidence: 91%
“…The highest prevalence of regular cycles (96%) was observed in 87 treated idiopathic-CPP girls during a 7-year follow-up period after the discontinuation of treatment (15). Jay et al (43) described menstrual cycle lengths as becoming increasingly regular, from 41% in the first year post-menarche to 65% at 3 or more years post-menarche (44).…”
Section: Reproductive Function and Risk Of Polycystic Ovarian Syndromementioning
confidence: 99%
“…2 Recently, a subcutaneous implant releasing the GnRHa histrelin at an average rate of 65 microg/day was developed, with encouraging results. 3,4 Monitoring of adequate suppression is usually based on an assessment of physical growth and puberty and the frequency of injections is often increased when these clinical parameters suggest inadequate suppression. Although there may be scope for further personalization of therapy, this has been difficult to achieve in the absence of objective and reliable tools that are simple, inexpensive and lend themselves to repeat measurements.…”
Section: Introductionmentioning
confidence: 99%